1997
DOI: 10.1111/j.1399-0039.1997.tb02858.x
|View full text |Cite
|
Sign up to set email alerts
|

Three newly identified A*24 alleles: A*2406, A*2413 and A*2414

Abstract: Three previously unknown A24-related alleles were identified by PCR-SSO typing and confirmed by DNA sequencing in Australian Aboriginal populations (A*2406, 2413) and in individuals of South American descent (A*2414). A*2406 and A*2413 both have two adjacent (but different) nucleotide substitutions in codon 156 in exon 3 compared to A*2402, resulting in a single amino acid replacement in each allele. The South American A*2414 is apparently a hybrid between A2 and A24 with a segment of the A*24 sequence between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Our analysis of the LIFT cohort found that Indigenous Australians display a restricted and distinct HLA profile in accordance with previously published serological studies 14 , 15 , 16 . Our molecular HLA typing verified the predominant usage of HLA‐A*02:01, 11:01, 24:02, 34:01 and HLA‐B*13:01, 15:21, 40:01/02, 56:01/02.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our analysis of the LIFT cohort found that Indigenous Australians display a restricted and distinct HLA profile in accordance with previously published serological studies 14 , 15 , 16 . Our molecular HLA typing verified the predominant usage of HLA‐A*02:01, 11:01, 24:02, 34:01 and HLA‐B*13:01, 15:21, 40:01/02, 56:01/02.…”
Section: Discussionsupporting
confidence: 90%
“…To support the rational design of an effective, broad‐spectrum universal vaccine, it is essential to define the dominant influenza‐specific T‐cell responses focused on the allelic HLA variants characteristic of Indigenous Australians 15 , 16 . Identification of immune and host factors underlying severe influenza disease in Indigenous Australians, highly susceptible to influenza, is of an enormous importance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations